Pengungkapan Corporate Social Responsibility dan Kinerja Keuangan Perusahaan Manufaktur Indonesia dan Malaysia - Cahyono, Dwi; Rachmaniyah, Aulia (Universitas Pendidikan Ganesha, 2020)
The study aims to analyze and investigate the effect of corporate social responsibility disclosure on the company’s performance and reputation measured by the price stock as well as to compare the level of corporate social responsibility disclosure between manufacturing companies in Indonesia and Malaysia. The research was conducted by selecting of 57 the Indonesia manufacturing company public listed on Indonesia Stock Exchange and 27 the Malaysia manufakturing company public listed on Malaysia Stock Exchange and using annual report in 2016-2018. The sample are determined by using purposived sampling technique. Analysis method used is a simple regression. Comparison of corporate social responsibility disclosure using independent sample t-test showed that there were significant difference between manufacturing companies in Indonesia and Malaysia in Indonesia and Malaysia.